Analysis And Evaluation of Currently Used Standards/Norms/Guidelines for the Design and Installation of Emergency Lighting - Marcin Ochenkowski; Tomasz Popielarczyk (Safety & Fire Technology)
Aim: The aim of this publication is to present the results of theoretical research - assessment of normative and legal documents used to design and install emergency lighting systems in selected countries. The aim of the research was to analyze and compare emergency lighting systems in Poland, against the background of selected standards from different parts of the world. Introduction: Seven standards were adopted for the analysis and assessment of currently used standards/norms/guidelines for designing and installing emergency lighting in the world, therefore differences in the approach to design are noticeable. The analysis took into account the guidelines and standards of countries such as: United Arab Emirates, United States, Australia, Netherlands, Norway, Great Britain and Poland. European countries base their design requirements on the European standard EN 1838 and EN 50172, taking into account their own guidelines. The requirements that appear in Australian and NFPA standards look slightly different, which were also an inspiration for the standards of the United Arab Emirates, which we can consider the best described and most rigorous. During the analysis, standards/guidelines were compared in terms of requirements for places requiring application, light intensity, type of lighting and installation of emergency lighting fixtures. The study also describes the requirements for dynamic lighting systems, for which there is no Polish standard and for now come from the German DIN VDE standard for visual evacuation guidance systems. Methodology: Theoretical research was used in the research process, such as: analysis of literature and legal documents, synthesis, generalization, inference, comparison and analogy. The analysis took into account guidelines and standards of countries such as: United Arab Emirates, United States, Australia, Netherlands, Norway, Great Britain and Poland. The selection of individual countries was guided by the level of development of these systems in a given country and the availability of source documents. Conclusions: Based on the analysis, it can be stated that in all the standards analyzed, the safe evacuation from a facility threatened by fire and loss of basic power supply is the most important. All countries also approach the issue of facilities in which these systems should be used in a similar way. The requirements in Europe are largely based on the EN 1838 standard, while the United States and the United Arab Emirates are based on the NFPA. The problem is the lack of a European standard for dynamic lighting systems, the current requirements come from the German standard DIN VDE V 0108-200 for Visual evacuation guidance systems, which will probably become an inspiration for the creation of the EN standard in the future. Keywords: emergency lighting, lighting fitting, nominal fail-safe working time, safety sign, dynamic escape routing systems (DSL)